Book Review: Untuk Mengenang Perempuan Itu: Rekonstruksi Teologis Feminis tentang Asal-usul Kekristenan - Naysalmin Lumbaa (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
The book “In Memory of Her” by Elisabeth Schüssler Fiorenza explores feminist theology and employs a feminist historical hermeneutic to recover the history of early Christianity. Fiorenza critiques the androcentric perspectives that dominate biblical interpretation and the reception of historical sources. She argues that readings exposing patriarchal bias are necessary to restore women’s roles within ecclesial narratives. Through a more egalitarian historical reconstruction, she highlights the contributions of women in the Jesus movement and the growth of early Christian communities—contributions that have long been marginalized. Her discussion of gender equality, particularly regarding the interpretation of Galatians 3:28, demonstrates that Christian teachings can be understood in a liberating and inclusive way. Although Fiorenza focuses on the context of the early church, she also questions modern patriarchal church structures and encourages transformative practices toward a more egalitarian community. Her method is unique in that she reconstructs church history through feminist hermeneutics. This distinguishes her work from Rosemary Radford Ruether, who develops an inclusive framework of liberation theology and ethics, and from Kwok Pui-lan, who analyzes colonial and racial power dynamics in biblical studies. This work makes a significant contribution to feminist theological studies. It creates space for a more egalitarian understanding of Christian history and the role of women in church tradition through an interdisciplinary approach integrating theology, history, and gender studies.